2024
DOI: 10.1037/spq0000563
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of early literacy and word reading skill development across the first 6 months of school and reading instruction.

Abstract: This study described the growth trajectories of 105 children (n = 55 boys) who had just started primary school in New Zealand (NZ). Children were assessed every fourth school week around 1.5 months after starting school, for five sessions on Dynamic Indicators of Basic Early Literacy Skills first sound fluency (FSF), AIMSweb letter sound fluency (LSF), and a newly created NZ word identification fluency (NZWIF-Y1), designed for alignment with beginning reading instruction in NZ. In addition to progress monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 43 publications
(173 reference statements)
3
7
0
Order By: Relevance
“…At the immediate post‐test, older pre‐schoolers in the SSS condition demonstrated benefits for their letter‐naming skills relative to ABC (Riordan et al, 2022), potentially reflecting a greater focus on print‐related literacy skills as children near school starting age in New Zealand. Children’s age also contributed to letter‐sound performance, in line with other NZ research showing that letter‐sound performance typically grows during children’s first year of school (Cameron et al, 2020; Cameron, Carroll, et al, 2023), potentially reflecting exposure to instruction. Cameron, Carroll, et al (2023) reported mean NWF‐correct letter sounds after 6 months of school ( M = 27.53, SD = 23.46), similar to the performance of children who participated in SSS in this study ( M = 26.00; SD = 22.88).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…At the immediate post‐test, older pre‐schoolers in the SSS condition demonstrated benefits for their letter‐naming skills relative to ABC (Riordan et al, 2022), potentially reflecting a greater focus on print‐related literacy skills as children near school starting age in New Zealand. Children’s age also contributed to letter‐sound performance, in line with other NZ research showing that letter‐sound performance typically grows during children’s first year of school (Cameron et al, 2020; Cameron, Carroll, et al, 2023), potentially reflecting exposure to instruction. Cameron, Carroll, et al (2023) reported mean NWF‐correct letter sounds after 6 months of school ( M = 27.53, SD = 23.46), similar to the performance of children who participated in SSS in this study ( M = 26.00; SD = 22.88).…”
Section: Discussionsupporting
confidence: 80%
“…Children’s age also contributed to letter‐sound performance, in line with other NZ research showing that letter‐sound performance typically grows during children’s first year of school (Cameron et al, 2020; Cameron, Carroll, et al, 2023), potentially reflecting exposure to instruction. Cameron, Carroll, et al (2023) reported mean NWF‐correct letter sounds after 6 months of school ( M = 27.53, SD = 23.46), similar to the performance of children who participated in SSS in this study ( M = 26.00; SD = 22.88).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations